The Role of Emotional Intelligence in Enhancing Effective Leadership - Hadimulya, Ihsan; Nurcahyo, Danang; Prasetya, Rico (Lentera Ilmu Nusantara, 2024)
In today’s organizational context, leaders are expected not only to think logically but also to be emotionally attuned in managing workplace interactions. This study seeks to explore how emotional intelligence contributes to building effective leadership. Using a qualitative methodology, data were collected through in-depth interviews and analyzed thematically. The results indicate that leaders with high levels of emotional intelligence are generally more capable of regulating emotions, fostering constructive workplace relationships, and cultivating a productive team environment. Emotional intelligence also plays a role in enhancing decision-making, resolving conflicts, and boosting team motivation. Within the Indonesian organizational culture, empathy and self-awareness emerge as vital components of effective leadership. Thus, enhancing emotional intelligence is a strategic effort in developing resilient, adaptable, and inspiring leaders.